Implementation of Subject System in Archiving of Criminal Case File of Limapuluh Policy Sector of Pekanbaru City - Putri Anastasia (Universitas Airlangga, 2022)
This study aimed to find out how to analyze the subject and archive metadata at the Limapuluh PoliceSector, Pekanbaru City. The method used is descriptive with mixed quantitative and qualitative, with a sample of 189 archives in the Criminal Investigation Unit of the Limapuluh Police Sector, Pekanbaru. Data collection techniques are observation, interviews, and documentation. The results showed that from a total of 189 archives, the percentage of archives was very high on the subject of theft as many as 139 archives (73.54%), followed by the subject of Embezzlement (6.88 %), Cheating and Fraud (4.76%),crimes against public order (4.23%), Crimes against morality (3.17%), Printing of Criminal Aid Receipts (3.70%.), Persecution (1.59%), Crimes Against People's Liberties (0.53%), Crimes Against Life (0.53%), Destroying or Damaging Goods, (0.53%), the Limapuluh Police Sector in Pekanbaru, has already put it efforts to matching the Metadata of the Police Archives. So that it has complied with provisions in inputting data into the register book. The Limapuluh Police Sector provided easy access to conventional metadata, within the year 2017 to 2019